Extra-renal Wilms’ Tumor in a child: A Case Report - Liaghat, Naeem; Rasul, Laraib; Salman, Zainab; Shahzad, Iqra (Iranian Journal of Pediatric Surgery, 2023)
Wilms’ tumor is one of the most common abdominal tumor of childhood, primarily a malignant renal tumor. Extrarenal wilms’ tumor, however, is a rare disease, more commonly reported in Indian subcontinent. The locations of an extrarenal wilms’ tumor include retroperitoneum, uterus, skin and thorax.